THE IMPLEMENTATION OF CHARACTER EDUCATION ON ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SENIOR HIGH SCHOOL 1 BENTENG, SELAYAR - Ponno Ponno; Saprin Saprin; Muh. Rapi (Universitas Islam Negeri Alauddin Makassar, 2021)
This article discusses the Implementation of Character Education in Islamic Religious Education Subjects at Senior High School 1 (SMA 1) Benteng, Selayar. This study uses qualitative research by analyzing existing information data, based on facts in the field. Data obtained through observation, interviews, documentation and drawing conclusions so that they can unravel the problem completely in accordance with the problems discussed. Implementation of planting character values to students. So the most important thing is the teacher's expertise in internalizing the character education. into all aspects of subjects that will be given to students in schools because character education is one of the main elements of religion that cannot be separated from Islamic teachings. That is why character education is integrated in Islamic Religious Education subjects.